Continuity and Stability in Development - Bornstein, Marc H. (2017)
Developmental science is concerned with both consistency and change in characteristics through time. Consistency and change in development are tracked by group mean-level continuity and individual-order stability. Group mean-level and individual-order consistency and change are both developmentally informative and can coexist conceptually and empirically as they are partially orthogonal perspectives on development. Continuity and stability are broadly applicable to characteristics of the individual, dyad, and environment. Without the distinctions between mean-level continuity and individual-order stability, researchers who use the terms willy-nilly leave their readers in the dark as to which feature of development is meant. In this article, we distinguish the two types of consistency and change, and discuss their measurement, importance, moderation, and implications.